Predictability of roller ski race time in elite female biathletes - Hill, M. R.; Osbeck, J. S.; Amico, V. J.; Rundell, K. W. (Medicine & Science in Sports & Exercise, 1995)
Running and roller-ski treadmill performances (measures were lactate profile, VO2peak) were correlated with the results of a 15 km international roller ski biathlon race. Roller-ski endurance-test and VO2peak correlated highly with event performance and together accounted for 97% of the variance in the race data. No relationship was observed between running treadmill and race results. Implication. Any physiological testing in roller-skiing is likely to be only valuable if it is sport specific. The convenience of running treadmills and testing situations will not make results any more valuable. No inferences can be drawn from running treadmill laboratory data and biathlon roller-ski race performances. The principle of specificity is particularly well-supported in this investigation. (see also http://www-rohan.sdsu.edu/dept/coachsci/vol12/hill2.htm)